Penilaian Hot-Fit Model Terhadap Penggunaan Sistem Informasi Manajemen Rumah Sakit Tk.II Kartika Husada Pontianak Tahun 2024 - Galuh Kusuma Dhewy; Agus Hadian Rahim; Mira Veranita (CV. ULIL ALBAB CORP, 2025)
The hospital at this time is different from the previous one, must adjust to existing developments. Data processing that used to be manual in the current era has been largely replaced by a digitization system. The Hospital Management Information System (SIMRS) is very important to support the efficiency of the management process in the hospital starting from information to patients, patient data, data processing and all activities in the hospital. Tk.II Kartika Husada Hospital Pontianak has used SIMRS but has not met the ongoing business process. Therefore, the evaluation of the SIMRSKH module that has been running will be carried out through the user. Because users using SIMRSKH directly know the modules that have been running in accordance with the business processes at Tk.II Kartika Husada Hospital. Not only that, by conducting evaluations, SIMRSKH will be able to be improved by finding problems from users. The purpose of the study is to obtain an overview of the use of SIMRS at Tk.II Kartika Husada Hospital from the beginning of its formation until now for assessment with the HOT-Fit Model, the obstacles faced, and solutions to existing problems. Interviews were conducted with 8 respondents and observations at the registration unit and outpatient unit. Based on the results of the research, SIMRS has sufficiently met the needs of the Registration Unit and Outpatient Unit even though some modules and features are not complete. The HOT-Fit Model found that the constraints were on the factors of Human, organization and technology. The recommendations of this study are in the form of readjusting the workforce in the Registration Unit, completing the SPO for the use of SIMRS, rejuvenating the internet network, ensuring that the patient's fingerprints are recorded properly and continuing the development of the system until it is complete.